Application of auricular acupoint massage combined with psychological nursing for a patient undergoing breast mass resection under local anesthesia (耳穴按摩联合术中心理护理在1例局部麻醉下乳腺肿物切除患者中的应用) - XIE Caixia (谢彩霞); TANG Ling (唐玲); CHEN Hong (陈宏); ZHANG Lei (张磊) (中西医结合护理)
This paper summarized the application effect of auricular acupoint massage and related psychological nursing measures for a patient undergoing breast mass resection under local anesthesia. Based on the analysis of the psychological characteristics of the patients before, during and after the surgery, corresponding psychological nursing and auricular acupoint massage were carried out. The Traditional Chinese Medicine nursing technology combined with psychological nursing is effective to reduce the psychological burden, relieve the anxiety, fear and other psychological discomfort, improve the tolerance and cooperation of patients to the operation, and ensure the success of operation and postoperative recovery. (本文总结1例局部麻醉下乳腺肿物切除患者运用耳穴按摩结合心理护理疗法的护理经验。护士针对患者术前、术中及术后出现的心理特征进行分析, 采用相应的心理护理方式和中医特色的耳穴按摩方法, 能有效减轻患者术前、术中及术后心理负担, 缓解焦虑、恐惧等心理不适, 提高患者对手术的耐受度和配合度, 有助于手术的顺利进行和患者术后的康复。)